Predictive Study on the Application of the Soweto Wind Turbine Results in the Coastal Region of South Africa - Sithole, T; Veeredhi, V; Sithebe, T (جامعة الوادي Université ofEl-Oued, 2023)
This study evaluates the performance of three wind turbine prototypes (Prototypes 1, 2, and 3) in Soweto, South Africa, by analyzing their monthly energy generation under different time of day/month conditions. Prototype 3 emerges as the most efficient, generating 39.5 W at a wind speed of 1.17 m/s and projecting a maximum of 40 kWh per month. Building upon these results, a predictive study examines the feasibility of implementing the same technology in coastal regions, specifically Gqeberha, where stronger winds prevail. Utilizing empirical data from Soweto, the study forecasts an improved energy output of up to 54.3 W at a wind speed of 5.16 m/s (18.6 km/h) and up to 100 kWh per month. The findings highlight the potential benefits of utilizing wind turbine technology in coastal areas, contributing valuable insights to renewable energy system development in similar geographical contexts.
Article
Keywords: Predictive study, Coastal regions, Soweto, Port elizabeth result.